INFLUENCE OF SPORTS AND EATING HABITS ON THE DEVELOPMENT OF RED-S (REMUNOM, 2025)
The term Relative Energy Deficiency Syndrome in Sport (RED-S) has been introduced and described, its cause being the reduced calorie intake in situations that demand high caloric intake, such as sports training. In this sense, physiological stress impairs performance and recovery. The objective of this study was to investigate the relationship between the development of RED-S and the impact of sports practiced on athletes' eating habits. Therefore, this study was conducted through an integrative review, relating the development of the syndrome to the type of sport and eating habits. The research was carried out by searching for articles in the PubMed, BVS, and ScienceDirect databases, using the descriptors selected from the Medical Subject Headings (MeSH) and Health Sciences Descriptors (DeCS): "Eating behavior" AND "Relative Energy Deficiency in Sport". Nine articles were selected, with a sample of 2,874 participants from different sports. The findings show that RED-S results from the interaction between inadequate eating habits. In aesthetic and weight-control sports such as ballets, gymnastics, and rowing, greater vulnerability is observed, even in team sports. Factors such as social pressure, excessive use of food delivery apps, and the cult of body image contribute to energy imbalances. Thus, it becomes essential to adopt multidisciplinary approaches that integrate nutritional education.